2018
DOI: 10.1515/abm-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Applying the theory of planned behavior to determine factors associated with physical activity by women with hypertension in rural areas of Iran

Abstract: Background Hypertension is the leading preventable cause of premature deaths worldwide. Physical activity reduces the levels of blood lipids and blood pressure in people suffering from hypertension. Objectives To apply the theory of planned behavior (TPB) to determine factors associated with physical activity by women with hypertension who were referred to health care centers in Kiashahr in 2016. Methods The present observational study was conducted in a cross-section of 215 women diagnosed with hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…According to the Theory of Planned Behavior, intention to perform the behavior is determined by attitude, subjective norms, and perceived behavioral control (Ajzen, 1991). Many studies regarding health-related behaviors have tested the Theory of Planned Behavior (e.g., Gabriel, Hoch, & Cramer, 2019;Hatefnia, Alizadeh, & Ghorbani, 2019). Among samples of nurses and nursing students, the Theory of Planned Behavior has been tested on the intention to report medication errors (Natan, Sharon, Mahajna, & Mahajna, 2017), child abuse (Atencion et al, 2019;Cho & Kim, 2016) and adverse events (Ekayani, Wardhani, & Rachmi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Theory of Planned Behavior, intention to perform the behavior is determined by attitude, subjective norms, and perceived behavioral control (Ajzen, 1991). Many studies regarding health-related behaviors have tested the Theory of Planned Behavior (e.g., Gabriel, Hoch, & Cramer, 2019;Hatefnia, Alizadeh, & Ghorbani, 2019). Among samples of nurses and nursing students, the Theory of Planned Behavior has been tested on the intention to report medication errors (Natan, Sharon, Mahajna, & Mahajna, 2017), child abuse (Atencion et al, 2019;Cho & Kim, 2016) and adverse events (Ekayani, Wardhani, & Rachmi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that deeper understanding of the mothers’ perceived barriers for performing these behaviors could offer important insights to develop effective efforts for reducing the gap between knowledge and behaviors. [ 41 ] Given that knowledge alone is not enough to change behavior[ 42 ] , attention to other variables such as enabling factors, subjective norms, and so on to increasing the effectiveness nutrition education interventions has been recommended. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…Chevance et al found that obese participants with habitual sedentary behavior held a more positive attitude to physical activity and performed at a higher objective level of physical activity [20]. A study suggested that attitude was significantly related to physical activity among women with hypertension in rural areas of Iran [21]. A recent study integrating selfdetermination theory into the research model demonstrated that attitude toward physical activity was a strong predictor of physical activity intention among college students in central China [22].…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%